International Visitors' Perspectives on Geopark Sustainability in Langkawi Island, Malaysia - Marzuki, Azizan; Mohamad, Diana; Jaafar, Mastura (Routledge, 2015)
Conventional knowledge has that the tourism industry offers four types of benefits to its participants, namely leisure, education, entertainment and social networking. The tourism industry that can be broadly encapsulated into groups of active-based and passive-based tourism activities is a subject with a complex organization structure. More importantly, the tourism industry is more than providing service to its participants. Its successfulness, reliability and validity are influenced by scores of factors including visitors’ attitudes. This study aims to seek the visitors’ attitudes on four tourism pillars (environment, economic, social and support systems) towards realizing sustainable tourism development movement. The study area is KILIM Geopark which is located in Langkawi Island, Malaysia. Assessment has been done to examine the relationships between income, education background and the studied variables. Overall observation shows that although many have been done, much more are needed to be implemented and achieved in order to improve, enhance and strengthen KILIM’s existing development model.